Automated Static Perimetry for diagnostics of visual field defects in glaucoma - S.B. Slobodyanyk (Ukrainian Society of Ophthalmologists, 2019)
Progression of glaucomatous optic neuropathy results in the development of specific visual field defects, which dictates the need for careful visual field testing in glaucoma patients in addition to monitoring intraocular pressure and the optic disc. Automated perimetry has made it possible to increase significantly the accuracy of visual field measurements and to simplify the examination and data evaluation. And built-in statistical packages have allowed for detection of minimal defects of visual fields and to predict the progression of glaucomatous optic neuropathy. The paper describes the basic principles of standard automated perimetry, variants of data reports and interpretation performance through the example of the Humphrey Visual Field Analyzer (Сarl Zeiss). Reliability indices, quantitative visual field indices (MD, PSD, and VFI) and their practical use for perimetry diagnostics of glaucomatous defects are described. Also, there are defined visual field defects, common for glaucoma. Finally, the paper describes how to use Guided Progression Analysis to follow up visual fields with the course of time and to detect statistically significant progression of visual field loss.